Pengaruh Kualitas Kehidupan Kerja, Insentif Dan Kepemimpinan Terhadap Kepuasan Kerja Pegawai Di Bank Btpn Kc Padang - Melati Nilam Putri; Prima Yulianti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze and explain the influence of work life quality, incentives, and leadership on employee job satisfaction at Bank BTPN Padang Branch Office. Job satisfaction is an important factor that affects employee performance and productivity in achieving organizational goals. A good quality of work life, a fair and transparent incentive system, as well as an effective leadership style, are believed to enhance job satisfaction among employees. However, in practice, there are still various issues regarding suboptimal employee job satisfaction levels, which require further research to identify the influencing factors. This research employs a quantitative approach using a survey method by distributing questionnaires to all employees of Bank BTPN Padang Branch Office. The sampling technique used is a census (total sampling), where the entire population is taken as the researchsample. The research findings show that work life quality, incentives, and leadership simultaneously have a significant influence on employee job satisfaction. Partially, work life quality has a positive and significant impact on job satisfaction, indicating that better work life quality leads to higher employee satisfaction. Incentives also have a positive and significant effect, suggesting that fair and transparent incentive distribution can increase employee motivation and satisfaction. Furthermore, leadership has a significant impact on job satisfaction, implying that a participative and communicative leadership style fosters a conducive work environment and enhances employee satisfaction.